2018
DOI: 10.1186/s12935-018-0669-x
|View full text |Cite
|
Sign up to set email alerts
|

Integrated whole genome microarray analysis and immunohistochemical assay identifies COL11A1, GJB2 and CTRL as predictive biomarkers for pancreatic cancer

Abstract: BackgroundPancreatic cancer is characterized by its unsatisfying early detection rate, rapid disease progression and poor prognosis. Further studies on molecular mechanism and novel predictive biomarkers for pancreatic cancer based on a large sample volume are required.MethodsMultiple bioinformatic analysis tools were utilized for identification and characterization of differentially expressed genes (DEGs) from a merged microarray data (100 pancreatic cancer samples and 62 normal samples). Data from the GEO an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…Besides, many studies have also demonstrated that the three genes may serve as promising biomarkers for cancer. For example, GJB2 promoted early stage breast cancer progression by regulating cancer stemness [28]; Zhu et al suggested that GJB2 was a prognostic marker in patients with pancreatic cancer by genome-scale analysis [29]; the group of Sun D found that GJB2 was identified as predictive biomarkers for pancreatic cancer by integrated whole genome microarray analysis and immunohistochemical assay [30]; Masuda et al indicated that overexpressed S100A2 was a prognostic marker for patients with stage II and III colorectal cancer [31]; Kwon et al showed that S100A2 was significant for progression of prostate adenocarcinoma [32]. Regrading to SPOCK2, the group of Ren F confirmed that SPOCK2 contributed to the progression of endometrial cancer by modulating the biological behavior of cancer cells [33].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, many studies have also demonstrated that the three genes may serve as promising biomarkers for cancer. For example, GJB2 promoted early stage breast cancer progression by regulating cancer stemness [28]; Zhu et al suggested that GJB2 was a prognostic marker in patients with pancreatic cancer by genome-scale analysis [29]; the group of Sun D found that GJB2 was identified as predictive biomarkers for pancreatic cancer by integrated whole genome microarray analysis and immunohistochemical assay [30]; Masuda et al indicated that overexpressed S100A2 was a prognostic marker for patients with stage II and III colorectal cancer [31]; Kwon et al showed that S100A2 was significant for progression of prostate adenocarcinoma [32]. Regrading to SPOCK2, the group of Ren F confirmed that SPOCK2 contributed to the progression of endometrial cancer by modulating the biological behavior of cancer cells [33].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, uncovering the mechanism of hypoxia-regulated responses in PC cells will aid in its treatment. PC; they had the potential to predict poor outcomes (Sun, Jin, Zhang, & Tan, 2018). Based on the gene expression profile of PC tissues in the TCGA database, YAP1 was identified as an independent prognostic marker and was associated with extracellular matrix remodelling (Zhou et al, 2020).…”
Section: Restoration Of Yeats2 Blocks the Inhibitory Effects Of Hifmentioning
confidence: 99%
“…Recently, it has been reported that several predicted models for risk estimation, such as S100P , ERO1LB , SULF1 , ITGA2 , GPRC5A, ACTN4, LMO2, p16INK4a and CLPS (Watanabe et al, 2015; Nakata et al, 2009; Gerdes et al, 2002; Lyu et al, 2018; Zhang et al, 2013; Ji et al, 2014; Zhu et al, 2017; Li et al, 2018; Liu et al, 2018). A study recently identified three genes COL11A1 , GJB2 and CTRL as prognostic biomarkers for PC by using integrated whole genome microarray analysis and immunohistochemical assay (Sun et al, 2018). Most existing prognosis models of PC involve only one gene or mRNA, which have their limitations.…”
Section: Discussionmentioning
confidence: 99%